Surface Triggered Self-Assembly of Fmoc-Tripeptide as an Antibacterial Coating - Criado-Gonzalez, Miryam; Iqbal, Muhammad Haseeb; Carvalho, Alain; Schmutz, Marc; Jierry, Loïc; Schaaf, Pierre; Boulmedais, Fouzia (Frontiers in Bioengineering and Biotechnology, 2020)
In western countries, one patient on twenty will develop a nosocomial infection during his hospitalization at health care facilities. Classical antibiotics being less and less effective, this phenomenon is expanding year after year. Prevention of bacteria colonization of implantable medical devices constitutes a major medical and financial issue. In this study, we developed an antibacterial coating based on self-assembled Fmoc-tripeptide. Fmoc-FFpY peptides (F: phenylalanine; Y: tyrosine; p: PO42-) are dephosphorylated enzymatically into Fmoc-FFY by action of alkaline phosphatase functionalized silica nanoparticles (NPs@AP), previously deposited on a surface. Fmoc-FFY peptides then self-assemble through π–π stacking interactions, hydrogen bonds and hydrophobic interactions adopting β-sheets secondary structures. The obtained hydrogel coatings show fibrillary structures observed by cryo-scanning electron microscopy with a thickness of few micrometers. At low concentration (≤ 0.5 mg.mL-1), self-assembled Fmoc-FFY has a superior antibacterial activity than Fmoc-FFpY peptide in solution. After 24 h of incubation, Fmoc-FFY hydrogel coatings fully inhibit the development of Gram-positive Staphylococcus aureus (S. aureus). The antibacterial effect is maintained on an in vitro model of repetitive infection in the case of S. aureus. This coating could serve in infections were Gram positive bacteria are prevalent, e.g. intravascular catheter infections. This work gives new insights towards the design of an alternative antimicrobial coating.